Soybean crop intensification for sustainable aboveground-underground plant–soil interactions - Singh, Ramesh Kumar; Upadhyay, Pravin Kumar; Dhar, Shiva; Rajanna, G. A.; Singh, Vinod Kumar; Kumar, Rakesh; Singh, Rajiv Kumar; Babu, Subhash; Rathore, Sanjay Singh; Shekhawat, Kapila; Dass, Anchal; Kumar, Amit; et al. (Frontiers in Sustainable Food Systems, 2023)
The major challenge of growing soybean, other than unfavorable weather and small farm size, is the non-availability of quality inputs at the right time. Furthermore, in soybean growing regions, crop productivity and soil environment have deteriorated due to the use of traditional varieties and conventional methods of production. Soybean crop intensification or system of crop intensification in soybean (SCI) is an agricultural production system that boosts soybean yields, improves the soil environment, and maximizes the efficiency of input utilization, although the contribution of SCI to crop productivity is not well understood as different genotypes of soybean exhibit different physiological responses. Therefore, a field study was conducted in 2014–2015 and 2015–2016 using three crop establishment methods (SCI at a 45 cm × 45 cm row spacing, SCI at 30 cm × 30 cm, and a conventional method at 45 cm × 10 cm) assisted in vertical strips with four genotypes (Pusa 9,712, PS 1347, DS 12–13, and DS 12–5) using a strip-plot design with three replications. Compared with standard methods of cultivation, the adoption of SCI at 45 cm × 45 cm resulted in a significantly higher stomatal conductance (0.211 mol H2O m−2 s−1), transpiration rate (7.8 mmol H2O m−2 s−1), and net photosynthetic rate (398 mol CO2 m−2 s−1). The implementation of an SCI at 30 cm × 30 cm had significantly greater intercepted photosynthetic active radiation (PAR) (1,249 mol m−2 s−1) than the conventional method system, increasing crop yield from 9.6 to 13.3% and biomass yield from 8.2 to 10.7%. In addition, under an SCI at 30 cm × 30 cm, there were more nodules, significantly larger root volume and surface density, and increased NPK uptake compared with the other methods. Significantly greater soil dehydrogenase activity, alkaline phosphatase activity, acetylene-reducing assay, total polysaccharides, microbial biomass carbon, and soil chlorophyll were found with SCI at 45 cm × 45 cm (13.63 g TPF g−1 soil hr.−1, 93.2 g p-nitro phenol g−1 soil hr.−1, 25.5 n moles ethylene g−1 soil hr.−1, 443.7 mg kg−1 soil, 216.5 mg kg−1 soil, and 0.43 mg g−1 soil, respectively). Therefore, the adoption of an SCI at 30 cm × 30 cm and/or 45 cm × 45 cm could provide the best environment for microbial activities and overall soil health, as well as the sustainable productivity of soybean aboveground.